An electromagnetic sensor for the autonomous running of visually impaired and blind athletes (Part II: The wearable device) - Pieralisi, M.; Di Mattia, V.; Petrini, V.; De Leo, A.; Manfredi, G.; Russo, P.; Scalise, L.; Cerri, G. (Sensors, 2017)
Currently, the availability of technology developed to increase the autonomy of visually impaired athletes during sports is limited. The research proposed in this paper (Part I and Part II) focuses on the realization of an electromagnetic system that can guide a blind runner along a race track without the need for a sighted guide. In general, the system is composed of a transmitting unit (widely described in Part I) and a receiving unit, whose components and main features are described in this paper. Special attention is paid to the definition of an electromagnetic model able to faithfully represent the physical mechanisms of interaction between the two units, as well as between the receiving magnetic sensor and the body of the user wearing the device. This theoretical approach allows for an estimation of the signals to be detected, and guides the design of a suitable signal processing board. This technology has been realized, patented, and tested with a blind volunteer with successful results and this paper presents interesting suggestions for further improvements.